Novel Resistant Starch Type 4 Products of Different Starch Origins, Production Methods, and Amounts Are Not Equally Fermented when Fed to Sprague‐Dawley Rats - Coulon, Diana B.; Page, Ryan; Raggio, Anne M.; Guice, Justin; Marx, Brain; Gourineni, Vishnupriya; Stewart, Maria L.; Keenan, Michael J. (Molecular nutrition & food research, 2020)
Scope The possible mechanisms of production of four novel resistant starch type 4 (RS4) products for total cecal fermentation in an in vivo rodent model are evaluated. Methods and results Forty weanling rats are randomly assigned to five groups (n = 8) for a 3‐week study. Starches are the RS type 4 products, as 10% of weight of RS diets (RSA–RSD), and AMIOCA starch (100% amylopectin) comprises 53.6% weight of control (CON) and 43.6% weight of RS diets. The RS products vary by percent purity and origin (potato, corn, tapioca). At euthanasia, cecal contents, serum, GI tract, and abdominal fat are collected. RSB, RSC, and RSD fed rats have greater empty cecum weights, lower cecal content pH, higher cecal content wet weight, and higher total cecal content acetate and propionate than the CON and RSA fed rats. Two other indicators of fermentation, total cecal contents butyrate and glucagon‐like peptide 1, do not have significant ANOVA F values, which require more subjects for 80% power. Conclusion RS4 products that are produced from different starch origins with varying amounts of RS4 content and different methods of production are not uniformly fermented in an in vivo model. Fermentation of dietary resistant starch is associated with positive gut health benefits. Rats are fed customized diets using one of four unknown resistant starch type 4 products. Three of the four products appear to be readily fermented by the rats. Fermentation of the product by an animal model can assess the potential benefits of these products as functional foods.